Smart power switch using internet of things - Abdulaziz Khalid Eid Abougamea; Siow Chun Lim (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The increase in electricity consumption coupled with the lack of a convenient way to assist the consumers to lower their electricity consumption is a growing concern. Smart internet of things (IoT)-based devices has been developed in this regard. However, no specific standards were followed, and this is a problem for the consumer as they have to own different smart device from different brands which results in higher cost. To solve these issues, a smart power switch using IoT is proposed. The system consists of microcontroller (ESP32), relay and current sensor (ACS712). The ACS712 measures the current of the appliance. The ESP32 then send these readings to server. Whenever the ESP32 receives switching commands from the cloud platform, ESP32 will activate the relay and hence switching the appliance. The cloud platform is linux based virtual private server (VPS) running on Django Python and structured query language (SQL) ite database. The mobile application built using flutter to allow both iOS and android users to use the app to control and monitor the normal appliances. The server, circuit and mobile application have showed a real-time data exchange, fast response, numerical, graphical consumption presentation and capable of setting energy or power limit for the appliance to not exceed.